(untitled) (Impetus, 2026)
To investigate the relationship between explosive strength and speed is essential to improve their performance and provide a deeper understanding of the different strategies and approaches that can be implemented in the training field. To determine the relationship of lower body explosive strength with acceleration speed in U17 soccer players. Adopting a positivist approach and using a quantitative design of correlational scope, a sample of 21 male soccer players from the department of Sucre-Colombia was examined. The 30-meter speed test and the SJ, CMJ and ABK jumps were carried out. Significant correlations were found (p<.05) between speed and explosive strength of players for different positions, it was also observed that midfielders and forwards exhibit higher levels of speed and power compared to goalkeepers and defenders. Strengthening players’ lower body could be crucial to improve their performance on the field. These findings not only have practical implications for training and physical preparation of soccer players but can also inform tactical and strategic decisions to optimize overall team performance.